2005
DOI: 10.1094/ats-2005-0117-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Bermudagrass Varieties from Divot Injury

Abstract: Intensively used turf areas in the southern United States are commonly established to bermudagrass (Cynodon dactylon (L.) Pers.C. dactylon × C. transvaalensis Burtt‐Davy), partly due to its good recuperative potential. However, little scientific data is available regarding recuperative differences among bermudagrass varieties. The objective of the following research was to quantify differences in injury recovery among the forty‐eight bermudagrass entries in the 2002 National Bermudagrass Test of the National T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 3 publications
5
35
0
Order By: Relevance
“…Although there were differences among bermudagrass cultivars across collection dates for clipping yield, they generally all had similar clipping yields. This is similar to previous rankings of divot recovery for bermudagrass cultivars (19).…”
Section: Clipping Yield Differences Among Cultivars and Speciessupporting
confidence: 91%
“…Although there were differences among bermudagrass cultivars across collection dates for clipping yield, they generally all had similar clipping yields. This is similar to previous rankings of divot recovery for bermudagrass cultivars (19).…”
Section: Clipping Yield Differences Among Cultivars and Speciessupporting
confidence: 91%
“…Because research has not been conducted to compare divot recovery of bermudagrass and zoysiagrass in the same experiment, discussion comparing our findings with previous work is limited to tests evaluating single species. Similar to these findings, Karcher et al (4,5) observed cultivar performance differences across collection dates in divot recovery for bermudagrass and zoysiagrass. For divot recovery of bermudagrass in 2003, Karcher et al (4) found that Princess 77, Patriot, and Riviera had faster divot recoveries than Tifsport and Tifway, which is similar to findings of this study on 29 June 2009.…”
Section: Differences Exist In Divot Recovery Among Bermudagrass and Zsupporting
confidence: 61%
“…El Toro had the fastest divot recovery in one year of the study, but had a relatively slower divot recovery in another year. Although bermudagrass and zoysiagrass were evaluated in separate experimental areas by Karcher et al (4,5), their data suggest that the recuperative capacity of these two species may not be as different as previously reported (1,10). For example, in 2004 Karcher et al (4) reported that Riviera bermudagrass required 4.6 days to reach 50% recovery, while in 2004 Karcher et al (5) reported that Palisades zoysiagrass required 4.2 days to reach 50% recovery.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations